2017
DOI: 10.1038/s41598-017-16618-5
|View full text |Cite
|
Sign up to set email alerts
|

Deleting the mouse Hsd17b1 gene results in a hypomorphic Naglu allele and a phenotype mimicking a lysosomal storage disease

Abstract: HSD17B1 is a steroid metabolising enzyme. We have previously generated knockout mice that had the entire coding region of Hsd17b1 replaced with lacZ-neo cassette (Hsd17b1-LacZ/Neo mice). This resulted in a 90% reduction of HSD17B1 activity, associated with severe subfertility in the knockout females. The present study indicates that Hsd17b1-LacZ/Neo male mice have a metabolic phenotype, including reduced adipose mass, increased lean mass and lipid accumulation in the liver. During the characterisation of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…The impact of local changes in gene expression on the phenotypic spectrum of targeted mouse mutants has not been thoroughly studied. However, an accumulating number of reports indicate that some phenotypes associated with a targeted gene mutation are causally related to off-target effects on neighboring genes (17-21). For example, mice with a homozygous disruption of the Ampd1 gene generated by a targeted trap mutation (knockout-first allele) die within two days post-natally, and show reduced body weight, decreased lung saccular space and lack of milk in their stomach (20).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of local changes in gene expression on the phenotypic spectrum of targeted mouse mutants has not been thoroughly studied. However, an accumulating number of reports indicate that some phenotypes associated with a targeted gene mutation are causally related to off-target effects on neighboring genes (17-21). For example, mice with a homozygous disruption of the Ampd1 gene generated by a targeted trap mutation (knockout-first allele) die within two days post-natally, and show reduced body weight, decreased lung saccular space and lack of milk in their stomach (20).…”
Section: Resultsmentioning
confidence: 99%
“…RNA-seq analysis revealed that expression of the neighboring Man1a2 and Nras genes was down-regulated in the knockout-first Ampd1 mice, but not in the conditional Ampd1 mutant mice. Another recent study reported that replacement of the coding region of the steroid metabolising enzyme gene Hsd17b1 with the lacZ gene inserted in the translation initiation site and a neo r selection cassette (Hsd17b1-LacZ/Neo mice) results in reduced adipose mass, increased lean mass and lipid accumulation in the liver of male mice (17). Further characterization revealed that the metabolic phenotype of Hsd17b1-LacZ/Neo mice is caused by the reduced expression of the immediate 5’ gene Naglu , which encodes the N-acetyl-alpha-glucosaminidase enzyme, and not by a deficiency in HSD17B1 activity.…”
Section: Resultsmentioning
confidence: 99%
“…The impact of local changes in gene expression on the phenotypic spectrum of targeted mouse mutants has not been thoroughly studied. However, an accumulating number of reports indicate that some phenotypes associated with a targeted gene mutation are causally related to off-target effects on neighboring genes (17)(18)(19)(20)(21). For example, mice with a homozygous disruption of the Ampd1 gene generated by a targeted trap mutation (knockout-first allele) die within 2 days postnatally and show reduced body weight, decreased lung saccular space, and lack of milk in their stomach (20).…”
Section: Erk3 Is Dispensable For Perinatal Survivalmentioning
confidence: 99%
“…RNA-seq analysis revealed that expression of the neighboring Man1a2 and Nras genes was downregulated in the knockout-first Ampd1 mice but not in the conditional Ampd1 mutant mice. Another recent study reported that replacement of the coding region of the steroid metabolizing enzyme gene Hsd17b1 with the lacZ gene inserted in the translation initiation site and a neo r selection cassette (Hsd17b1-LacZ/Neo mice) results in reduced adipose mass, increased lean mass, and lipid accumulation in the liver of male mice (17). Further characterization revealed that the metabolic phenotype of Hsd17b1-LacZ/Neo mice is caused by the reduced expression of the immediate 5= gene Naglu, which encodes the N-acetyl-␣-glucosaminidase enzyme, and not by a deficiency in HSD17B1 activity.…”
Section: Erk3 Is Dispensable For Perinatal Survivalmentioning
confidence: 99%
“…We have previously demonstrated that replacing the coding region of the HSD17B1 gene by a LacZ reporter results in marked down‐regulation in the expression of Naglu that is located upstream of the Hsd17b1 gene (29). To exclude the possibility that the male fertility phenotype in HSD17B1KO originates as a result of the down‐regulation of Naglu expression, we also analyzed male fertility and testis histology of NAGLUKO.…”
Section: Resultsmentioning
confidence: 99%